Hemoperitoneum secondary to mesenteric laceration after abdominal trauma - Case report. (April 2021) - Ferreira, Marta M.; Guimarães, Narcisa; Mónica, Inês Bolais; Oliveira, Simone; Pais, Daniela; Andrade, Sara; Fonseca, Alice; Couceiro, Ana; Borges, Isabel; Cecílio, José Valente
Abstract: Mesenteric laceration is an uncommon cause of hemoperitoneum, with nonspecific signs and symptoms and frequently is camouflaged by the signs of other traumatic lesions. There is a high risk to go unnoticed increasing morbidity and mortality. We report a case of a 43-year-old man, who was involved in a motorcycle accident, with thoraco-abdomino-pelvic trauma, but without evidence of intra-abdominal lesions on exams, with exception of hemoperitoneum. Due to hemodynamic instability, it was performed an exploratory laparotomy. Intraoperative findings were mesenteric lacerations affecting a small bowel segment. This case demonstrates that a high index of suspicion is necessary to diagnose and treat lesions like mesenteric laceration, not visible early on imaging but potentially fatal, with high risk of complications.